A concise geography of Belgium : National Committee of Geography of Belgium, IGU, 2012. - National Committee of Geography of Belgium (Ghent : Academia Press, 2012)
This volume presents to English-speaking audiences a summary of the main findings of the 'Third National Atlas of Belgium', recently published in Belgium as a six-volume set. Based on a decade of geographic and socioeconomic research, 'A Concise Geography of Belgium' includes topics such as urban and rural landscapes, agriculture, housing and living environment, and social demography. These atlases are highly valuable to scholars of geography in general and Belgian geography and history in particular.
Physiography and geology -- The North Sea -- Climate -- Landscapes -- The making of the Belgian space -- Cities -- Housing -- Population -- Economic aspects -- Transport infrastructure -- Geodetic and cartographical standards applied in Belgium -- Belgian cartographic institutions -- Geography at Belgian universities.
Includes bibliographical references (page 46).
Keywords: Belgium -- Geography; Belgium -- Maps; Ruimtelijke planning en ruimtelijk ontwerp -- Methoden en technieken